POSITIONING MIE SEDAAP MELALUI IKLAN TV DAN PENGARUHNYA TERHADAP PEMBELIAN ULANG MAHASISWA PENDIDIKAN EKONOMI STKIP PGRI SUMATERA BARAT - Wahyuni, Sri (Jurnal Pelangi : Research of Education and Development, 2014)
This study aimed to determine 1) how much influence the positioning of Mie Sedaap Through TV commercials based on the attributes, price and quality, aspects of the use or manufacture, the uniqueness of the product with the intention of buying a competitor to the education of students of Economics STKIP West Sumatra PGRI 2) how much influence the positioning Mie Sedaap based on attributes through the intention to buy TV ads Economic education students STKIP PGRI West Sumatra 3) the influence of positioning Mie Sedaap through TV advertising rates are based on the intention to buy the education of students of Economics STKIP PGRI West Sumatra 4) how much influence the positioning of Mie Sedaap based aspects of the use or way through the making of the TV ad buy against the purpose of education student STKIP Economic PGRI West Sumatra 5) how much influence the positioning of Mie Sedaap based uniqueness of products through TV ads against the intention to buy the education of students of Economics STKIP PGRI West Sumatra. Type of research is descriptive quantitative. The population of this research is the education of students of Economics STKIP PGRI West Sumatra. While the size of the sample of 92 people with the sampling technique in this study is purposive sampling. This type of data is the primary data by using questionnaire data collection techniques. The analysis technique used is descriptive analysis consisting of: classical assumption test, multiple regression analysis, T test and Test F. The results of this study were 1) Positioning Mie Sedaap through TV ads jointly influence the purchase of re-education student STKIP Economic PGRI West Sumatra. 2) Positioning Mie Sedaap based attributes through repeated TV ads influence purchase STKIP Economic education students PGRI West Sumatra. 3) Positioning by price Mie Sedaap through TV advertising influences repeat purchase STKIP Economic education students PGRI West Sumatra 4) Positioning Mie Sedaap based aspects of the use or manner of making purchases through repeated TV ads affect the education of students of Economics STKIP PGRI West Sumatra. 5) Positioning Mie Sedaap based uniqueness of the product through TV advertising influences repeat purchase STKIP Economic education students PGRI West Sumatra